Case Report: A Chinese Family of Type A Insulin Resistance Syndrome With Diabetes Mellitus, With a Novel Heterozygous Missense Mutation of the Insulin Receptor Gene - You, Wei; Yang, Jianming; Wang, Lu; Liu, Yanqun; Wang, Wen; Zhu, Li; Wang, Wei; Yang, Jun; Chen, Fangyuan (Frontiers in Endocrinology, 2022)
Type A Insulin resistance syndrome (TAIRS) is an autosomal dominant or recessive genetic disorder caused by insulin dysfunction resulting from insulin receptor (INSR) gene mutation. The main features of TAIRS include hyperinsulinemia, abnormal glucose metabolism and changes in acanthosis nigricans. We identified a TAIRS family with a novel heterozygous missense gene mutation type in China. One patient from the Chinese Han family exhibiting signs and symptoms of TAIRS were presented for evaluation. Whole-exome sequencing revealed a heterozygous mutation.Both the patient proband and his father were identified with insulin receptor exon 19c.3472C>T(p.Arg1158Trp),which resulted in a missense mutation that led to replace by a base in the amino acid codon. We found that the he patient proband and his father exhibited high insulin and C-peptide release after glucose stimulation by insulin and C-peptide release tests. At the same time, we also ruled out the possibility of islet βcell tumor through relevant examinations.These findings indicate that the INSR gene mutation may cause pancreatic β cell functional impairment and contribute to the development of diabetes.